PENGARUH MOTIVASI KERJA; DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN - Saluy, Ahmad Badawi; Treshia, Yuwinta (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2018)
The research was conducted at PT IE with the aim to analyze the influence of work Motivation; work Discipline; and Compensation to employee’s Performance. Data collection was done using a questionnaire directly to 90 people considered as saturated and the analysis of data using Statistic analysis with coefficient of determination and a multiple linear regression. The result showed that: (i) work motivation partially has a positive and significant effect to employee’s performance; (ii) work discipline partially has a positive and significant effect to employee’s performance and (iii) compensation partially has a positive and significant effect to employee’s performance.(iv)Simultaneously or works together; there was a positive and significant effect among variables; work motivation; work discipline and compensation to employee’s performance. The third of independent variables; work motivation; work discipline; compensation each have partially effect and also can works together and have positives effect and significant to employee’s performance; for that can be proved with all result of hypothesis and proved.